Synthesis and Characterization of Niobium Oxide Nanoparticles, Polyindole and Nb2O5/Polyindole Nanocomposite - Anandhi, S.; Keerthika, D.; Edward, M. Leo; Jaisankar, V. (Asian Journal of Chemistry, 2020)
In present work, polyindole-Nb2O5 nanocomposite was synthesized and characterized by various analytical methods. Niobium oxide nanoparticles were prepared by sol gel method. Polyindole and Nb2O5 nanocomposites was prepared by chemical polymerization method and the morphology of Nb2O5 nanoparticles, polyindole and the nanocomposite was studied by SEM. The chemical structure of Nb2O5 nanoparticle, polyindole and the nanocomposite was characterized by UV-visible, FTIR and NMR spectroscopic techniques. Elemental composition and chemical character was analyzed by the use of EDAX technique. The X-ray powder diffraction technique was used to determine the degree of crystallinity and crystallite sizes. Thermal analysis such as TGA and DSC showed that the conducting polymers in the nanocomposites were stable even at high temperatures.